Dreamworlds of Alabama - Shelton, Allen (Allen C.) (University of Minnesota Press, 2007)
Wisteria draped on a soldiers coffin, sent home to Alabama from a Virginia battlefield. The oldest standing house in the county, painted gray and flanked by a pecan orchard. A black steel fence tool, now perched atop a pile of books like a prehistoric bird of prey. In Dreamworlds of Alabama, Allen Shelton explores physical, historical, and social landscapes of northeastern Alabama. His homeplace near the Appalachian foothills provides the setting for a rich examination of cultural practices, a place where the language of place and things resonates with as much vitality and emotional urgency a.